Fast Screening Method for Nitrogen Reduction Reaction (NRR) Electrocatalytic Activity with Rotating Ring‐Disc Electrode (RRDE) Analysis in Alkaline Environment. Issue 24 (28th October 2020) - Ferrara, Marcello; Bevilacqua, Manuela; Tavagnacco, Claudio; Vizza, Francesco; Fornasiero, Paolo
Abstract: The Haber‐Bosch process for NH3 production leads to a considerable greenhouse gas release due to the remarkable use of fossil fuels. Therefore, there is an increasing interest in developing alternative and environmental friendly approaches. Among the possible solutions, the electrocatalytic conversion of N2 has recently gained significant attention; on the other hand, not only scientific but also important technical aspects remain fundamental issues to be clarified. Particularly relevant is the need to improve the analytical protocols to ascertain that any detected NH3 is actually produced from N2 rather than from any external contaminations or partial decomposition of the catalyst itself. Here, a rotating ring‐disc electrode (RRDE) setup is used for the first time to study the N2 electroreduction process with the aim to recognize the product species formed at the disc and detected at the ring electrodes, respectively. We demonstrated that this experimental approach is effective to discern also a low‐level ammonium concentration through monitoring the ammonia oxidation peak at the ring electrode for a fast and preliminary electrocatalytic performance evaluation and to prevent false positives. The versatility of the RRDE method employed as a fingerprint of new electrocatalyst candidates could allow to reserve time and cost. Abstract : Detect, faster, better : Rotating ring disk electrode‐based analysis for the nitrogen reduction reaction represent a fast preliminary approach to identify promising candidate electro‐catalysts for a sustainable ammonia electro‐synthesis and it appears effective to discern also low‐levels ammonium concentration. Moreover, CVs on platinum ring can detect N2 H4 side product and reveal catalyst modification and/or degradation. Finally, hydrogen interference from HER in aqueous environments can be minimized by optimizing the system setup.